Need Fulfillment in Intercollegiate Student-Athletes’ Dual Roles: A Mixed-Methods, Person-Oriented Investigation - Raabe, Johannes; Readdy, Tucker; McHenry, Lauren; Leyhr, Daniel; Ryan, Tara (Journal of Intercollegiate Sport, 2022)
Individuals competing in varsity intercollegiate sport are tasked with managing the dual roles of athletes and students. The purpose of current study was to simultaneously explore student-athletes’ perceived satisfaction of autonomy, competence and relatedness in sport and academics. A mixed-methods, person-oriented design was utilized. Quantitative data was collected with a sample of N = 238 student-athletes from various varsity intercollegiate sports. For sport, four clusters were revealed: ‘Low Need Satisfaction,’ ‘Moderately Low Need Satisfaction,’ ‘Moderate Relatedness,’ and ‘High Need Satisfaction.’ For academics, four clusters were revealed: ‘Low Need Satisfaction,’ ‘Moderate Relatedness,’ ‘Moderate Autonomy and Competence,’ and ‘High Need Satisfaction.’ Reflexive thematic analysis of semi-structured interviews with a sub-sample of n = 12 student-athletes representing all clusters revealed four themes: (a) global factors sensitized student-athletes to the experience of basic psychological needs, (b) contextual factors determined fluctuations in student-athletes’ need fulfillment, (c) student-athletes perceived interaction effects in the satisfaction of the three basic psychological needs within the same domain, and (d) student-athletes’ sport participation had a cross-contextual influence on their need fulfillment in academics. Findings provide an understanding of student-athletes’ perceived basic psychological needs across the achievement domains of academics and sport.